Experimental investigation on the seismic response of a steel liquid storage tank equipped with floating roof by shaking table tests. - De Angelis, M.
In this paper, the effectiveness of the base isolation on steel storage tanks has been investigated through numerical models and then checked by shaking table tests on a reduced scale (1:14) model of a real steel tank, typically used in petrochemical plants. In the experimental campaign the floating roof has also been taken into account. The tests have been performed on the physical model both in fixed and isolated base configurations; in particular two alternative base isolation systems have been used : high-damping rubber bearings devices and sliding isolators with elasto-plastic dampers. Finally, a comparison between experimental and numerical results has also been performed.
Keywords: Steel storage tanks; Floating roof; Shaking table test; Base isolation